God was in Christ an essay on incarnation and atonement - Baillie, Donald MacPherson, 1887-1954 (London, UK Faber and Faber, 1955)
Includes bibliographical references and index.
Keywords: Lord's supper -- theology; Christology; Jesus Christ -- person and offices